Influence of a Salt Plume Parameterization in a Coupled Climate Model. (27th September 2018) - Sidorenko, D.; Koldunov, N. V.; Wang, Q.; Danilov, S.; Goessling, H. F.; Gurses, O.; Scholz, P.; Sein, D. V.; Volodin, E.; Wekerle, C.; Jung, T.
Abstract: Sea ice formation is accompanied by the rejection of salt which in nature tends to be mixed vertically by the formation of convective plumes. Here we analyze the influence of a salt plume parameterization in an atmosphere‐sea ice‐ocean model. Two 330‐yearlong simulations have been conducted with the AWI Climate Model. In the reference simulation, the rejected salt in the Arctic Ocean is added to the uppermost ocean layer. This approach is commonly used in climate modeling. In another experiment, employing salt plume parameterization, the rejected salt is vertically redistributed within the mixed layer based on a power law profile that mimics the penetration of salt plumes. We discuss the effects of this redistribution on the simulated mean state and on atmosphere–ocean linkages associated with the intensity of deepwater formation. We find that the salt plume parameterization leads to simultaneous increase of sea ice (volume and concentration) and decrease of sea surface salinity in the Arctic. The salt plume parameterization considerably alters the interplay between the atmosphere and the ocean in the Nordic Seas. The parameterization modifies the ocean ventilation; however, resulting changes in temperature and salinity largely compensate each other in terms of density so that the overturning circulation is not significantly affected. Plain Language Summary: The process of salt rejection during the sea ice formation is not properly parameterized in the climate models. Here we implement the salt plume parameterization in an atmosphere‐ice‐ocean model and analyze its influence on the simulated mean state and associated atmosphere–ocean linkages. Salt plume parameterization leads to simultaneous increase of sea ice (volume and concentration) and decrease of sea surface salinity in the Arctic. It is argued that salt plume parameterization alters the interplay between the atmosphere and the ocean in the Nordic Seas. Key Points: A salt plume parameterization for the Arctic Ocean has been implemented into the AWI Climate Model The salt plume parameterization leads to simultaneous increase of sea ice (volume and concentration) and decrease of sea surface salinity in the Arctic It is argued that the salt plume parameterization alters the interplay between the atmosphere and the ocean in the Nordic Seas